THE EFFECT OF APPLYING TEACHING METHOD ON ENGLISH LEARNING PROCESS IN ISLAMIC EDUCATION STUDY - Fuziernisa Fahmi (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2022)
Learning a foreign language is a good first step to being able to communicate with other people to face the challenges of globalization, but simply knowing other people's languages ​​without mastering it in daily communication is not enough to meet the needs of globalization. Because in the era of globalization, the rapid development of communication technology makes distance not an obstacle to getting information from various parts of the world. Thus, it is increasingly clear that mastery of foreign languages ​​such as English is needed in the learning process.